Marginal gap, cement thickness, and microleakage of 2 zirconia crown systems luted with glass ionomer and MDP-based cements - (:unkn) unknown (Academy of General Dentistry, 2014)
This in vitro study evaluated the marginal gap, cement thickness, and microleakage of glass-ionomer cement (GIC) and phosphate monomercontaining resin cement (MDP-RC) under 2 zirconia crown systems (Cercon and DC-Zirkon). Forty human premolars were prepared for all-ceramic zirconia crowns with a 1 mm circumferential finish line and a 1.5 mm occlusal reduction. The crowns (n = 10 per group) from each zirconia system were randomly divided into 2 groups and cemented either with GIC (Vivaglass CEM) or MDP-RC (Panavia F 2.0) cement. The cemented crowns were thermocycled 5000 times (5°-55°C). The crowns were immersed in 0.5% basic fuchsine dye solution for 24 hours and sectioned buccolingually and mesiodistally. Specimens were examined under optical microscope (100X). Data were analyzed using Student t-test and chi-square tests (α = 0.05). Mean marginal gap values for Cercon (85 ± 11.4 μm) were significantly higher than for DC-Zircon (75.3 ± 13.2 μm) (P = 0.018). The mean cement thickness values of GIC (81.7 ± 13.9 μm) and MDP-RC (78.5 ± 12.5 μm) were not significantly different (P = 0.447). Microleakage scores did not demonstrate significant difference between GIC (P = 0.385) and MDP-RC (P = 0.631) under Cercon or DC-Zircon. Considering the cement thickness values and microleakage scores obtained, both zirconia crown systems could be cemented in combination with either GIC or MDP-RC. © Copyright 2014 by the Academy of General Dentistry. All rights reserved.
Keywords: Glass ionomer cement; Marginal gap; Microleakage; Resin cement; Zirconia